The Analysis Figurative Meaning Of Jakarta Post A Paper - Dewi Mutiara Indah Ayu; Sjafty Nursitti Maili (Deiksis, 2016)
The purpose of this research is to know any kind of Figurative Meanings, which is dominantly used and to find out kinds of situation used in the Jakarta Post Headline News. The data were collected by qualitative research; they were gathered by doing newspaper observation. There were 14 headline news of Jakarta post collected. The data were analyzed by figurative meaning which consists of: personification, synecdoche, metonymy. The result of the study shows that Metonymy (3), Synecdoche (6), Personification (5), and the most dominant of figurative meaning are Synecdoche (6). This figurative meaning used in all situations that show expression in which the name of an attribute or a thing is substituted by another with which it is associated closely.Key words: Figurative Meanings Analysis, Headline News Jakarta Post